Oocyte-granulosa cell interactions during mouse follicular development: regulation of kit ligand expression and its role in oocyte growth - Thomas, Fiona H; Vanderhyden, Barbara C (Reproductive biology and endocrinology, 2006)
Ovarian folliculogenesis is regulated by both endocrine and intraovarian mechanisms that coordinate the processes of oocyte growth and somatic cell proliferation and differentiation. Within the follicle, paracrine interactions between the oocyte and surrounding granulosa cells are critical for normal cell development and function. This review focuses on the role of paracrine interactions during early oocyte and follicular development that ensure proper coordination of oocyte and somatic cell function. Particular emphasis is given to granulosa cell-derived Kit Ligand (KitL), whose functional importance for oocyte growth has been demonstrated by a wide range of in vivo and in vitro studies. Reported interactions between KitL and oocyte-derived growth differentiation factor-9 (GDF9) and bone morphogenetic protein-15 (BMP15) suggest the molecular basis of oocyte-granulosa cell interactions, but also hint at the complexity of these communications. These paracrine interactions and the structure of the oocyte-granulosa cell interface are follicle stage-specific and regulated by FSH. Elucidation of the molecular mechanisms that promote the development of healthy oocytes with good developmental competence has potential applications for improving fertility and for in vitro growth systems for oocytes from domestic animals and humans.